Розробка номенклатури ергономічних показників якості одягу - Палагнюк, Ю. В.; Слітюк, О. О. (Eastern-European Journal of Enterprise Technologies, 2009)
The offered block diagram of ergonomic parameters will allow to raise quality of development of clothes, to carry out a rating of quality in view of a complex parameter of ergonomic requirements. The structure and model of system for a rating of a complex ergonomic parameter of quality of clothes can be a basis for development of the project of the standard by definition of quality indicators of clothes